Parents’ Strategies for Taking Care of Their Child with Disability: The Challenges of Being Parents of a Child with Cerebral Palsy in the Danish Social Welfare System - Louise Bøttcher; Jesper Dammeyer (Scandinavian Journal of Disability Research)
Being the parent of a child with disability can be difficult. Research with a biomedical approach focuses on intrafamilial or intrapsychic challenges, while the social model and critical disability studies point to social barriers in an ableist society. As a third option, cultural-historical theory understand disability as relational and changeable in the intersection between persons and specific socio-cultural conditions. The aim of this study was to investigate how parents of children with cerebral palsy (CP) addressed problems at this intersection by developing care-taking strategies in relation to the Danish welfare system. Focus group interviews with 32 parents were completed. Findings showed that parents developed complex and elaborate strategies for how to struggle for welfare services for their child. The consequences of having a child with CP hinge on parents’ ability to learn to manage the mismatch between the needs of their child and social conditions shaped by the welfare system.